2001
DOI: 10.1074/jbc.m106928200
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Prion Proteins Are Partially Retained in the Endoplasmic Reticulum

Abstract: Familial prion diseases are linked to point and insertional mutations in the prion protein (PrP) gene that are presumed to favor conversion of the cellular isoform of PrP to the infectious isoform. In this report, we have investigated the subcellular localization of PrP molecules carrying pathogenic mutations using immunofluorescence staining, immunogold labeling, and PrPgreen fluorescent protein chimeras. To facilitate visualization of the mutant proteins, we have utilized a novel Sindbis viral replicon engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
93
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 41 publications
16
93
0
Order By: Relevance
“…Pulse-chase labeling experiments indicated that mutant PrP molecules misfold very soon after synthesis in the endoplasmic reticulum (ER) (6), raising the possibility that they are recognized as abnormal by the ER quality control machinery, and diverted to ER-associated degradation (ERAD). Consistent with this hypothesis, it was observed that several mutant PrPs were present at low levels on the cell surface, and localized in intracellular compartments, including the ER and cytoplasm (7)(8)(9)(10). It was also found that the proteasome inhibitor ALLN (Ac-Leu-Leu-NorLeu-al) affected the metabolism and cellular localization of PrP molecules carrying the amber mutation Y145stop, and the Q217R substitution linked to GSS (11,12).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Pulse-chase labeling experiments indicated that mutant PrP molecules misfold very soon after synthesis in the endoplasmic reticulum (ER) (6), raising the possibility that they are recognized as abnormal by the ER quality control machinery, and diverted to ER-associated degradation (ERAD). Consistent with this hypothesis, it was observed that several mutant PrPs were present at low levels on the cell surface, and localized in intracellular compartments, including the ER and cytoplasm (7)(8)(9)(10). It was also found that the proteasome inhibitor ALLN (Ac-Leu-Leu-NorLeu-al) affected the metabolism and cellular localization of PrP molecules carrying the amber mutation Y145stop, and the Q217R substitution linked to GSS (11,12).…”
supporting
confidence: 66%
“…In cultured, non-neuronal cells mouse PrP molecules carrying the D177N and nine-octapeptide mutations adopt an abnormal conformation soon after synthesis in the ER (6), and at the steady state they appear to accumulate in the ER and Golgi because their transit out of these organelles is delayed (9,16). Here we provide evidence that the same holds true for mutant PrPs synthesized in primary neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But studies with a series of mutants associated with transmissible spongiform encephalopathies indicated that most mutants that reside outside the hydrophobic region do not form detectable transmembrane forms (9). Instead, they are partially retained in the ER, which suggests misfolding and retention by the ER quality-control system (10). Recent understanding of protein folding and quality-control mechanisms has revealed that many misfolded secretory proteins are retained in the ER and subject to retrograde transport to the cytoplasm and degradation by the proteasome (11)(12)(13).…”
mentioning
confidence: 99%
“…These studies have revealed that some, but not all mutants, display PrP Sc -like biochemical properties including aggregation propensity as well as resistance to proteases and a GPI-specific phospholipase (Lehmann and Harris, 1996;Priola and Chesebro, 1998). Correlating with these abnormal biochemical properties, some mutants display altered subcellular localization, including partial retention in the ER (Ivanova et al, 2001), or retrotranslocation into the cytoplasm with subsequent degradation by the proteasome (Lorenz et al, 2002). Interestingly, some disease-associated PrP mutants are identical to wild-type PrP in terms of their biochemical properties and cellular distribution (Harris, 2003), raising the possibility that these molecules are pathogenic, not because they misfold and aggregate, but because the mutation subtly alters a physiological activity normally associated with PrP C .…”
Section: Mutant Prp Molecules Associated With Inherited Prion Diseasesmentioning
confidence: 99%